Assessment and Adoption of Tomato Charcoal Cooler Storage Bin for Farmers in The Tropics - Chukwuemeka Jude Ohagwu; Amarachukwu Violet Ohagwu; Nwaeze Joel Nwakaire (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2021)
The study tends to study the postharvest technological evaluation of different tomato storage environments/media for domestic preservation of fresh and fleshy tomato quality to improve its shelf life with emphasis on charcoal cooler storage bin (CCB). It involved the preliminary investigation of farmers’ knowledge and skill with regard to tomato preservation and storage with different tomato storage environments, adoption of developed CCB: design capacity was 40kg/batch storage for 7days in Nsukka. These were conducted between April to September, 2019. The field studies were carried out through structured questionnaire to know the adaptive knowledge and skill of farmers with regard to tomato preservation and storage. Comparative study of the developed CCB with other environmental storage conditions namely: open-air (ambient) storage (OAS), refrigerator (RF), freezer (FR), (room) laboratory storage (LS), and thatched house storage (THS) were carried out. The four varieties of fresh and fleshy harvested tomato fruits: Copra, Nindo F1, Yolings, and UTC locally cultivated were set into the 6 treatments (media), each treatment was replicated twice. The study showed that the quality attributes such as cracking, yellowing, weight loss, rottening, hardness, and brix value were determined. Based on the physicomechanical parameters of the tomatoes under seven days investigation, FR (0 °C,95%) and RF (10 °C, 85%) had better quality and prolonged shelf life, followed closely by the tomato CCB storage (12 °C,85%) and THS(12 °C,78%) then LS(25 °C,78%) and OAS(30 °C,78%). FR storage inhibited/delayed (cold stress) ripening with minimum weight loss, as compared to the other treatments in terms of stability in all parameters. Similarly, CCB was close to RF storage and performed significantly better than ambient OAS and LS. OAS and LS exhibited higher weight loss, and rapid ripening to deterioration due to tropical temperature and relative humidity fluctuation. Therefore, CCB is recommended for rural small scale farmers.